THE ROLE OF VIRTUAL TECHNOLOGIES IN DEVELOPING PROFESSIONAL COMPETENCE IN THE METHODOLOGY OF TEACHING MATHEMATICS (International journal of artificial intelligence, 2026)
This article analyzes the role of virtual technologies in developing the professional competence of future teachers within the framework of the methodology of teaching mathematics. The significance of virtual learning environments, digital programs, interactive simulations, and online platforms in the educational process is highlighted. Furthermore, the effectiveness of virtual tools in fostering mathematical thinking, creativity, logical reasoning, and problem-solving skills in students is examined.